Hubungan Karakter Religious terhadap hasil belajar peserta didik pada muatan pelajaran agama islam - Puji Utami; Juwita Saputri; Roy Andre Ferdinan; Naufal Aqila Kusnadi (Cahaya Ilmu Cendekia Publisher, 2022)
Research objectives: This study aims to determine the relationship between the character of social care and the learning outcomes of students in class V, theme 4, sub-theme 1 of learning 3,